Application of a liquid nitrogen direct jet system to the extinguishment of oil pool fires in open space. Issue 2 (16th August 2016) - Shi, Bobo; Zhou, Fubao
Abstract : Liquid fuel fires occurring during industrial processes are serious safety concerns around the world due to their devastating impact on lives, the environment and property. In this study, a liquid nitrogen delivery system was set up to extinguish the oil pool fires in open space. Effects of liquid nitrogen flow rate, pipe diameter, and liquid nitrogen release distance on the suppression process were analyzed according to the mass loss, burning rate and temperature variations. When liquid nitrogen release distance was 0.50 m and pipe diameter was 0.04 m, fire extinguishing time was the shortest 1.6 s and the temperature decrease rate above the liquid fuel surface reached 275°C/s. Fuel surface cooling and blow off process were revealed through the experiments as two kinds of fire extinguishing mechanisms. Based on the flame images captured by high speed camera, the flame expansion phenomenon might occur early in liquid nitrogen injection, especially the situation of the higher flow rate of liquid nitrogen. Three approaches (ground fixed system, moving transportation, and directional transportation of liquid nitrogen) are provided for fire extinguishment of large scale fires. The results obtained provide important reference for the conduct of fire extinguishment for fires. © 2016 American Institute of Chemical Engineers Process Saf Prog 36: 165–177, 2017